The Origin of the Galaxy and Local Group Saas-Fee Advanced Course 37 Swiss Society for Astrophysics and Astronomy - Bland-Hawthorn, Joss.; Freeman, Kenneth; Matteucci, Francesca; Moore, Ben.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This volume contains the updated and expanded lecture notes of the 37th Saas-Fee Advanced Course organised by the Swiss Society for Astrophysics and Astronomy. It offers the most comprehensive and up to date review of one of the hottest research topics in astrophysics - how our Milky Way galaxy formed. Joss Bland-Hawthorn & Ken Freeman lectured on Near Field Cosmology - The Origin of the Galaxy and the Local Group. Francesca Matteucci’s chapter is on Chemical evolution of the Milky Way and its Satellites. As designed by the SSAA, books in this series – and this one too – are targeted at graduate and PhD students and young researchers in astronomy, astrophysics and cosmology. Lecturers and researchers entering the field will also benefit from the book.
Keywords: Astronomy; Astrophysics; Astronomy, Astrophysics and Cosmology